Slag agent and preparation method thereof as well as purification method and application of solar Czochralski crystal silicon finishing section crucible bottom material

By using slag agent composed of CaO, SiO2, Al2O3, Na2O, Li2O and carbon black, combined with rotary heating and cooling solidification technology, the problem of low utilization of silicon material in the finished section of straight-pull crystalline silicon is solved, and the effect of efficient removal of metal impurities and improving the utilization of silicon material is achieved.

CN119640385APending Publication Date: 2025-03-18SICHUAN GOKIN SOLAR TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411868969.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The current silicon material utilization rate in the finished section of straight-pull crystalline silicon is low, resulting in the problem of waste of silicon material and low yield.

Method used

A slag agent composed of CaO, SiO2, Al2O3, Na2O, Li2O and carbon black is used to remove metal impurities in the base of the finished pot by rotary heating and cooling and solidification, and improve the utilization rate of silicon material.

Benefits of technology

Effectively remove metal impurities in the base of the finished pot, improve the utilization rate of silicon material, reduce silicon waste, reduce energy consumption, simplify the purification process, and significantly improve the purification effect of silicon material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640385A_ABST
    Figure CN119640385A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of semiconductors, in particular to a slag agent and a preparation method thereof as well as a purification method and application of a solar Czochralski crystal silicon finishing section crucible bottom material. The slag agent is mainly prepared from the following components in parts by mass: 16.2 to 28.8 parts of CaO, 41.2 to 53.8 parts of SiO2, 8 to 12 parts of Al2O3, 10 to 14 parts of Na2O, 1 to 5 parts of Li2O and 3 to 7 parts of carbon black. According to the slag agent, the formula is reasonable, all the components are combined according to a certain proportion and have a synergistic effect, metal impurities enriched in the crucible bottom material at the finishing section can be effectively removed, and therefore the utilization rate of the crucible bottom material is increased, and silicon waste is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of semiconductor technology, and in particular to a slag agent and a preparation method thereof, and a purification method and application of a crucible bottom material of a solar direct-pulled silicon finishing section. Background Art

[0002] When the silicon is pulled to the end, a large amount of metal impurities are often accumulated at the bottom of the crucible. In order to reduce the output of scrapped products, more than 100kg of silicon liquid is usually left at the bottom of the crucible. However, this part of silicon material can basically not be used again in crystal pulling after solidification, resulting in waste of silicon material. In order to improve the quality of the silicon rods after the end, the material fed to the end stage is usually the most expensive pure polysilicon.

[0003] The existing CZ silicon finishing stage has problems such as low silicon material utilization, high loss, high unit price, low crystal pulling yield and quality.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a slag agent and a preparation method thereof, a purification method and application of the crucible bottom material of the solar direct-pulled silicon finishing section, wherein the slag agent can effectively remove the metal impurities enriched in the crucible bottom material of the finishing section, thereby improving the utilization rate of the crucible bottom material.

[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0007] One aspect of the present invention relates to a slag agent, which is mainly made of the following components in parts by mass:

[0008] CaO 16.2-28.8 parts, SiO 2 41.2~53.8 parts, Al 2 O 3 8 to 12 servings, Na 2 O 10-14 parts, Li 2 O 1 to 5 parts and carbon black 3 to 7 parts.

[0009] The slag agent has a reasonable formula, and each component is combined in a certain ratio and acts synergistically, which can effectively remove the metal impurities enriched in the crucible bottom material of the finishing section, thereby improving the utilization rate of the crucible bottom material and reducing the waste of silicon.

[0010] Another aspect of the present invention also relates to a method for preparing the slag agent, comprising the following steps:

[0011] After mixing the components, they are heated to melt, cooled and ground.

[0012] The method for preparing the slag agent is simple, easy to operate, and does not rely on complex process equipment. The prepared slag agent can effectively remove impurity metals enriched in the crucible bottom material of the solar direct-pulled silicon completion section, thereby improving the utilization rate of the crucible bottom material of the solar direct-pulled silicon completion section.

[0013] Another aspect of the present invention also relates to a method for purifying the crucible bottom material of the solar CZ silicon finishing section, comprising the following steps:

[0014] The slag agent is mixed with the finishing stage feed, and then subjected to rotation heating treatment and cooling solidification.

[0015] The method for purifying the crucible bottom material of the solar direct-pull silicon finishing stage adds a slag agent to the finishing stage feed, and further proposes the crucible bottom material in coordination with the directional solidification technology, thereby improving the utilization rate of the crucible bottom material. The method uses the natural crystallization process of silicon liquid to complete the purification, which is a low-cost and high-efficiency solution that can make full use of the remaining life of the crucible and the residual material at the bottom of the crucible, simplify the purification process, reduce energy consumption, have obvious purification effects, and improve the utilization rate of silicon materials.

[0016] Another aspect of the present invention also relates to a solar direct-pulled silicon crystal method, including a method for purifying the crucible bottom material of the solar direct-pulled silicon crystal finishing section.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) The slag agent provided by the present invention has a reasonable formula, and the components are combined in a certain ratio and work synergistically, which can effectively remove the metal impurities enriched in the bottom material of the finished crucible, thereby improving the utilization rate of the bottom material of the crucible and reducing the waste of silicon.

[0019] (2) The method for preparing the slag agent provided by the present invention is simple and easy to operate, and does not require reliance on complex process equipment. The prepared slag agent can effectively remove the impurity metals enriched in the crucible bottom material of the solar direct-pulled silicon finishing stage.

[0020] (3) The present invention provides a method for purifying the crucible bottom material of the solar direct-pull silicon finishing stage, which adds a slag agent to the finishing stage feed, and further proposes the crucible bottom material in coordination with the directional solidification technology, thereby improving the utilization rate of the crucible bottom material. This method uses the natural crystallization process of silicon liquid to complete the purification, which is a low-cost and high-efficiency solution that can make full use of the remaining life of the crucible and the residual material at the bottom of the crucible, simplify the purification process, reduce energy consumption, have obvious purification effects, and improve the utilization rate of silicon materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 A schematic diagram of the purification process of the crucible bottom material of the solar CZ silicon finishing stage provided by the present invention. DETAILED DESCRIPTION

[0023] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0024] One aspect of the present invention relates to a slag agent, which is mainly made of the following components in parts by mass:

[0025] CaO 16.2-28.8 parts, SiO 2 41.2~53.8 parts, Al 2 O 3 8 to 12 servings, Na 2 O 10-14 parts, Li 2 O 1 to 5 parts and carbon black 3 to 7 parts.

[0026] In some specific embodiments, CaO may be, for example but not limited to, at least one of 16.2 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, or 28.8 parts, or a range value between any two of them.

[0027] In some specific embodiments, SiO 2 For example, it may be, but is not limited to, at least one of 41.2, 43, 45, 47, 49, 51 or 53.8 points, or a range value between any two of them.

[0028] In some specific embodiments, Al 2 O 3For example, it may be, but is not limited to, a point value of at least one of 8, 9, 10, 11 or 12, or a range value between any two of them.

[0029] In some specific embodiments, Na 2 O can be, for example, but not limited to, a point value of at least one of 10 parts, 11 parts, 12 parts, 13 parts, or 14 parts, or a range value between any two of them.

[0030] In some specific embodiments, Li 2 O can be, for example, but not limited to, a point value of at least one of 1 part, 2 parts, 3 parts, 4 parts, or 5 parts, or a range value between any two of them.

[0031] In some specific embodiments, the carbon black may be, for example, but not limited to, at least one of 3 parts, 4 parts, 5 parts, 6 parts, or 7 parts, or a range of values ​​between any two of them.

[0032] The slag agent has a reasonable formula, and the components are combined in a certain ratio and work synergistically to oxidize the metal impurities enriched in the bottom material of the finishing section to form precipitation, which can effectively remove the metal impurities enriched in the bottom material of the finishing section, thereby improving the utilization rate of the bottom material and reducing the waste of silicon.

[0033] When the silicon crystal is pulled to completion, a large amount of metal impurities are often enriched at the bottom of the crucible. These enriched metal impurities appear in the silicon liquid as interstitial positions and have a high affinity for slag. Impurity elements such as Al and Ca are first oxidized by the slag to form metal oxides with higher boiling points and insoluble in silicon liquid. Finally, under the action of gravity, the slag and the melt are gradually separated. Fe is rarely removed by slag refining technology because it is difficult to oxidize, but the reduction of Al and Ca concentrations is conducive to reducing the segregation coefficient of Fe in silicon, thereby further improving the purification effect of directional solidification.

[0034] Furthermore, the slag agent is mainly made of the following components in terms of mass fraction:

[0035] CaO 18-25 parts, SiO 2 44-50 parts, Al 2 O 3 9 to 11 servings, Na 2 O 11-13 parts, Li 2 O 2 to 4 parts and carbon black 4 to 6 parts.

[0036] Furthermore, the particle size of the slag agent is 65-75 μm, including but not limited to any point value of 65 μm, 67 μm, 69 μm, 71 μm, 73 μm or 75 μm or any range value between two of them. Controlling the particle size of the slag agent within a certain range can increase the specific surface area of ​​the slag agent and improve the oxidation effect. If the particle size is too small, it will float on the surface of the silicon liquid, and if the particle size is too large, it will directly precipitate, both of which will affect the impurity removal effect.

[0037] Another aspect of the present invention also relates to a method for preparing the slag agent, comprising the following steps:

[0038] After mixing the components, they are heated to melt, cooled and ground.

[0039] The slag preparation method is simple, easy to operate, and does not rely on complex process equipment. The prepared slag can effectively remove impurity metals enriched in the crucible bottom material of the solar direct-pulled silicon completion section, thereby improving the utilization rate of the crucible bottom material of the solar direct-pulled silicon completion section.

[0040] Furthermore, the cooling is performed in air.

[0041] Furthermore, the particle size of the ground material is 65-75 μm, including but not limited to any point value of 65 μm, 67 μm, 69 μm, 71 μm, 73 μm or 75 μm or a range value between any two of them.

[0042] Another aspect of the present invention also relates to a method for purifying the bottom material of the crucible of the solar CZ silicon finishing section, such as Figure 1 As shown, the following steps are included:

[0043] The slag agent is mixed with the finishing stage feed, and then subjected to rotation heating treatment and cooling solidification.

[0044] Solar CZ silicon, also known as CZ monocrystalline silicon, is a silicon single crystal with a certain size, crystal orientation, conductivity type and resistivity range that is pulled vertically from silicon melt. It has the advantages of high purity, excellent electrical and optical properties, and is an important raw material for manufacturing solar cells, semiconductor materials, and flat panel display devices.

[0045] The method for purifying the crucible bottom material of the solar direct-pull silicon finishing stage adds a slag agent to the finishing stage feed, and further proposes the crucible bottom material in coordination with the directional solidification technology, thereby improving the utilization rate of the crucible bottom material. The method uses the natural crystallization process of silicon liquid to complete the purification, which is a low-cost and high-efficiency solution that can make full use of the remaining life of the crucible and the residual material at the bottom of the crucible, simplify the purification process, reduce energy consumption, have obvious purification effects, and improve the utilization rate of silicon materials.

[0046] The finishing section mentioned in the present invention refers to the crystal pulling process of completing the crystal pulling of a silicon rod.

[0047] The finishing stage feeding mentioned in the present invention refers to the feeding when the silicon rod pulling is completed, including the remaining silicon material of the previous rod and the newly added silicon material.

[0048] Furthermore, the slag agent is 1% to 5% of the mass of the finished stage feed, including but not limited to any point value of 1%, 2%, 3%, 4% or 5% or any range value between the two. Adding an appropriate amount of slag agent can fully remove metal impurities in the bottom material of the finished stage crucible, and can also avoid excessive use of slag agent, which causes unnecessary waste.

[0049] Further, the temperature of the rotary heating treatment is 1450-1650°C, including but not limited to any point value of 1450°C, 1470°C, 1490°C, 1500°C, 1530°C, 1550°C, 1560°C, 1570°C, 1580°C, 1590°C, 1600°C, 1610°C, 1620°C, 1630°C, 1640°C or 1650°C or any range value between two thereof. Limiting the temperature of the rotary heating treatment within a certain range can ensure that the slag agent is fully melted and fully interacts with the feeding of the finishing stage.

[0050] Furthermore, the time of the rotary heating treatment is 8 to 12 minutes, including but not limited to any one of 8 minutes, 9 minutes, 10 minutes, 11 minutes or 12 minutes, or a range between any two of them.

[0051] Furthermore, the rotation speed of the rotary heating treatment is 5-8 rpm, including but not limited to any point value of 5 rpm, 6 rpm, 7 rpm or 8 rpm or any range value between two of them. The slag after impurity removal can be concentrated on the crucible wall by a certain rotation speed, and only the finished section material after impurity removal remains in the crucible.

[0052] Further, the cooling and solidification speed is 5 to 20 μm / S, including but not limited to any point value of 5 μm / S, 7 μm / S, 9 μm / S, 11 μm / S, 13 μm / S, 15 μm / S, 17 μm / S, 19 μm / S or 20 μm / S or a range value between any two of them. In order to more effectively form columnar crystals, the cooling and solidification speed is limited to a certain range.

[0053] Furthermore, the method for purifying the crucible bottom material of the solar CZ silicon finishing section is as follows: Figure 1 As shown, it also includes:

[0054] The amorphous area of ​​the finished section crucible bottom material obtained after cooling and solidification is removed to obtain a purified finished section crucible bottom material.

[0055] After cooling and solidification, the top and bottom of the finished crucible bottom material are amorphous areas, and the middle part is a columnar crystal area. The silicon material in this part is purified and usable silicon material. The silicon material in the amorphous areas at the top and bottom and the excess slag at the interface can be cut off to obtain the purified finished crucible bottom material.

[0056] Another aspect of the present invention also relates to a solar direct-pulled silicon crystal method, including a method for purifying the crucible bottom material of the solar direct-pulled silicon crystal finishing section.

[0057] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0058] Example 1

[0059] The slag agent provided in this embodiment is mainly made of the following components in terms of weight:

[0060] CaO 16.2 parts, SiO 2 53.8 copies, Al 2 O 3 10 servings, Na 2 O 12 parts, Li 2 O 3 parts and carbon black 5 parts.

[0061] Example 2

[0062] The slag agent provided in this embodiment is mainly made of the following components in terms of mass fraction:

[0063] CaO 20 parts, SiO 2 50 parts, Al 2 O 3 10 servings, Na 2 O 12 parts, Li 2 O 3 parts and carbon black 5 parts.

[0064] Example 3

[0065] The slag agent provided in this embodiment is mainly made of the following components in terms of weight:

[0066] CaO 23.3 parts, SiO 2 46.7 parts, Al 2 O 310 servings, Na 2 O 12 parts, Li 2 O 2 parts and carbon black 5 parts.

[0067] Example 4

[0068] The slag agent provided in this embodiment is mainly made of the following components in terms of mass fraction:

[0069] CaO 26.3 parts, SiO 2 43.7 parts, Al 2 O 3 10 servings, Na 2 O 12 parts, Li 2 O 3 parts and carbon black 5 parts.

[0070] Example 5

[0071] The slag agent provided in this embodiment is mainly made of the following components in terms of mass fraction:

[0072] CaO 28.8 parts, SiO 2 41.2 parts, Al 2 O 3 10 servings, Na 2 O 12 parts, Li 2 O 3 parts and carbon black 5 parts.

[0073] Example 6

[0074] The method for purifying the crucible bottom material of the solar CZ silicon finishing section provided in this embodiment comprises the following steps:

[0075] (1) The slag agent is put into the crucible at 4% of the mass ratio of the finished stage feed, mixed with the finished stage feed, and then subjected to a rotary heating treatment. The rotation speed of the rotary heating treatment is 5 rpm, the power is increased, and the temperature is raised to 1600° C. until the slag agent is completely melted. The temperature is kept for 10 minutes. The slag agent will be concentrated on the crucible wall due to the rotation of the crucible;

[0076] (2) gradually reducing the heater power for cooling and solidification to control the solidification rate to 15 μm / s until the silicon body is completely cooled;

[0077] (3) Take out the crucible, cut off the amorphous silicon at the top and bottom of the silicon ingot and the excess slag at the interface, and obtain the purified finished crucible bottom material.

[0078] Example 7

[0079] The method for purifying the crucible bottom material of the solar CZ silicon finishing stage provided in this embodiment is different from that in Embodiment 6 only in that the slag agent is added into the crucible at 1% of the mass ratio of the finishing stage feed material.

[0080] Example 8

[0081] The method for purifying the crucible bottom material of the solar CZ silicon finishing stage provided in this embodiment is different from that in Embodiment 6 only in that the slag agent is added into the crucible at 2% of the mass ratio of the finishing stage feed material.

[0082] Example 9

[0083] The method for purifying the crucible bottom material of the solar CZ silicon finishing stage provided in this embodiment is different from that in Embodiment 6 only in that the slag agent is added into the crucible at 3% of the mass ratio of the finishing stage feed material.

[0084] Example 10

[0085] The method for purifying the crucible bottom material of the solar CZ silicon finishing stage provided in this embodiment is different from that in Embodiment 6 only in that the slag agent is added into the crucible at 5% of the mass ratio of the finishing stage feed material.

[0086] Embodiment 11

[0087] The method for purifying the crucible bottom material of the solar CZ silicon finishing section provided in this embodiment is different from that in Embodiment 6 only in that the solidification rate is 5 μm / s.

[0088] Example 12

[0089] The method for purifying the crucible bottom material of the solar CZ silicon finishing section provided in this embodiment is different from that in Embodiment 6 only in that the solidification rate is 10 μm / s.

[0090] Embodiment 13

[0091] The method for purifying the crucible bottom material of the solar CZ silicon finishing section provided in this embodiment is different from that in Embodiment 6 only in that the solidification rate is 20 μm / s.

[0092] Comparative Example 1

[0093] The slag agent provided in this comparative example is mainly made of the following components in terms of weight:

[0094] CaO 35 parts, SiO 2 35 parts, Al 2 O 3 10 servings, Na 2 O 12 parts, Li 2 O 3 parts and carbon black 5 parts.

[0095] Comparative Example 2

[0096] The method for purifying the crucible bottom material of the solar CZ silicon finishing stage provided in this embodiment is different from that in Embodiment 6 only in that the slag agent is added into the crucible at 8% of the mass ratio of the finishing stage feed material.

[0097] Comparative Example 3

[0098] The method for purifying the crucible bottom material of the solar CZ silicon finishing section provided in this embodiment is different from that in Embodiment 6 only in that the solidification rate is 25 μm / s.

[0099] Experimental example

[0100] The purification effect is compared by comparing the difference between the iron content of the silicon material before purification (c1) and the iron content of the columnar crystals after purification (c2).

[0101] Calculation formula:

[0102] Table 1 Iron removal effect of different slag agent addition amounts

[0103]

[0104] From Table 1, we can see that as the proportion of CaO increases, the iron removal effect increases, but it exceeds SiO 2 The effect decreases after 80%; as the slag-agent mass ratio increases, the iron removal effect increases, but it is not recommended to exceed 5%.

[0105] Table 2 Iron removal effect at different solidification rates

[0106]

[0107]

[0108] It can be seen from Table 2 that different solidification rates have an impact on the iron removal effect.

[0109] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A slag agent, characterized in that: According to the mass percentage, it is mainly made of the following components: CaO 16.2-28.8 parts, SiO2 41.2-53.8 parts, Al2O3 8-12 parts, Na2O 10-14 parts, Li2O 1-5 parts and carbon black 3-7 parts.

2. The slag agent according to claim 1, characterized in that: The slag agent is mainly made of the following components in terms of mass fraction: CaO 18-25 parts, SiO2 44-50 parts, Al2O3 9-11 parts, Na2O 11-13 parts, Li2O 2-4 parts and carbon black 4-6 parts.

3. The slag agent according to claim 1 or 2, characterized in that: The particle size of the slag agent is 65-75 μm.

4. The method for preparing the slag agent according to any one of claims 1 to 3, characterized in that: The following steps are involved: After mixing the components, they are heated to melt, cooled and ground.

5. A method for purifying the bottom material of the crucible of the solar CZ silicon finishing stage, characterized in that: The following steps are involved: The slag agent according to any one of claims 1 to 3 is mixed with the finishing stage feed, and then subjected to a rotary heating treatment and a cooling solidification.

6. The method for purifying the crucible bottom material of the solar CZ silicon finishing section according to claim 5, characterized in that: The slag agent is 1% to 5% of the mass of the feed material in the finishing stage.

7. The method for purifying the crucible bottom material of the solar CZ silicon finishing section according to claim 5, characterized in that: The temperature of the rotary heating treatment is 1450-1650°C; And / or, the time of the rotary heating treatment is 8 to 12 minutes.

8. The method for purifying the crucible bottom material of the solar CZ silicon finishing section according to claim 5, characterized in that: The rotation speed of the rotation heating process is 5 to 8 rpm.

9. The method for purifying the crucible bottom material of the solar CZ silicon finishing section according to claim 5, characterized in that: The cooling and solidification speed is 5 to 20 μm / S.

10. A solar direct-pull silicon method, characterized in that: The invention comprises a method for purifying the crucible bottom material of the solar CZ silicon finishing section as described in any one of claims 5 to 9.